2010
DOI: 10.2967/jnumed.109.072462
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-Siderophores for PET Imaging of Invasive Pulmonary Aspergillosis: Proof of Principle

Abstract: The diagnosis of invasive pulmonary aspergillosis (IPA) is difficult and lacks specificity and sensitivity. In the pathophysiology of Aspergillus fumigatus, iron plays an essential role as a nutrient during infection. A. fumigatus uses a specific and highly efficient iron uptake mechanism based on iron-complexing ferric ion Fe(III) siderophores, which are a requirement for A. fumigatus virulence. We aimed to evaluate the potential of siderophores radiolabeled with 68 Ga, a positron emitter with complexing prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 21 publications
8
113
0
Order By: Relevance
“…Especially in the field of preclinical imaging, an increasing number of biologicals including small molecules, antibodies, their fragments and peptides have been developed and evaluated for imaging infectious diseases (24)(25)(26)(27)(28). Recently, attempts have been made to visualize IPA in A. fumigatus-infected animals with microPET/CT using 68 Ga radiolabeled siderophores (29,30). These small high-affinity chelating compounds are produced by fungi and bacteria to scavenge iron from the host, and by Gram-negative bacterial pathogens as virulence factors (31 TAFC has been shown to occur under conditions of iron depletion, patients who acquire fungal infections typically suffer from iron overload thereby potentially reducing tracer uptake and sensitivity of this method.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the field of preclinical imaging, an increasing number of biologicals including small molecules, antibodies, their fragments and peptides have been developed and evaluated for imaging infectious diseases (24)(25)(26)(27)(28). Recently, attempts have been made to visualize IPA in A. fumigatus-infected animals with microPET/CT using 68 Ga radiolabeled siderophores (29,30). These small high-affinity chelating compounds are produced by fungi and bacteria to scavenge iron from the host, and by Gram-negative bacterial pathogens as virulence factors (31 TAFC has been shown to occur under conditions of iron depletion, patients who acquire fungal infections typically suffer from iron overload thereby potentially reducing tracer uptake and sensitivity of this method.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that A. fumigatus faces iron limitation during mammalian infection: (i) Defects impairing adaptation to iron limitation, such as inactivation of the siderophore system or the iron regulator HapX, attenuate virulence in murine models of pulmonary aspergillosis (3, 5, 21); (ii) RIA and the siderophore system are transcriptionally up-regulated during initiation of murine infection (22); and (iii) TAFC-chelated 68 Ga, the uptake of which is induced by iron starvation, allows in vivo PET imaging of invasive pulmonary aspergillosis in rats (23). Consistent with these findings, human protection against A. fumigatus includes growth inhibition by polymorphonuclear leukocytes via lactoferrin-mediated iron depletion and possibly siderocalin-mediated scavenging of siderophores (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 years after the first attempts of labelling siderophores with 67 Ga [36-38, 40, 41], we evaluated the use of 68 Ga labelled siderophores for PET imaging of fungal infections [47]. In proof of concept studies, which should confirm or refute the possibility of PET imaging of infections caused by Aspergillus fumigatus (A. f.) using 68 Ga-siderophores [48], it was demonstrated that desferrisiderophores, particularly triacetylfusarinine C (TAFC), can be easily radiolabelled with 68 Ga using a few micrograms of the siderophore and exhibit high chemical stability. Uptake of 68 Ga-TAFC by A. f. was upregulated under iron starvation conditions and could be blocked with an excess of siderophore or NaN 3 , indicating specific and energy-dependent uptake.…”
Section: Siderophores For Molecular Imaging Of Infectionmentioning
confidence: 99%